Theoretical Foundations Of Creating A Conceptual Model Of The Given - Obidjonova, Shalola; Sobirjonov , Behzod (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article discusses the process of creating a conceptual data model, its purpose, and its importance in database design. A conceptual model visually represents the structure of data, identifies relationships between entities, and helps build an efficient and well-organized database. The concepts of entities, attributes, and relationships are explained, along with the main stages of developing a conceptual model. This approach ensures clarity, systematic organization, and improved data management efficiency.